Constructing and implementing of an autonomous vacuum cleaner - Marquínez, Cesar (2023)
The objective of this project is an implementation that entails the design and development of a low-cost vacuum cleaner that performs its autonomous operation. The detection of obstacles with the use of a sensor is the platform that allows the autonomy of the vacuum cleaner since these types of devices usually need the control and movement of a human for their job. The notion of low cost is given since its components are affordable. The autonomous vacuum cleaner uses an HC-SR04 ultrasonic sensor that emits an ultrasound that travels through air and if there is an obstacle in the way, it can avoid it by managing its behaviour through Arduino UNO. An autonomous vacuum cleaner gives us an overview and scalability of how open-source tools are leveraged for foundations of electronic projects and strategies’ use of Internet of Things (IoT) and Artificial Intelligence.